A Rubric to Assess Expository Texts - Melguizo-Moreno, Elisabeth (2020)
Teaching communicative competences to future teachers has become a need for the European Higher Education Area (EHEA). In this regard, it is essential to know the writing competence of the teachers in training and, specifically, their skills when it comes to writing a text. For that reason, this research article aimed to validate an analytical rubric to evaluate expository texts written by university students. The tool has taken into consideration seven general dimensions assessed according to an estimation scale, ranging from excellent to deficient, including good and acceptable. The validation of the tool was carried out using a mixed methodology (quantitative-qualitative), in which initially 12 independent judges validated its content, and then a statistical validation with the statistical package software (SPSS) was conducted. The results were the obtention of the unanimity of judgment among judges and high internal consistency in the tool. Therefore, the rubric has the suitable construct validity, validated by the judges’ assessment, and high reliability, which justifies its usefulness in analyzing and assessing expository texts to be written by future university students and teachers in training.